2009
DOI: 10.1007/s11239-009-0350-2
|View full text |Cite
|
Sign up to set email alerts
|

Mild hypothermia markedly reduces ischemia related coronary t-PA release

Abstract: "Mild hypothermia markedly reduces ischemia related coronary t-PA release." Journal of thrombosis and thrombolysis, 2009 Jun 5 http://dx.doi.org/10.1007/s11239-009-0350-2Access to the published version may require journal subscription.Published with permission from: Springer Methods: Sixteen 25-30 kg pigs were anesthetized and a temperature of 37°C was established using an intravascular cooling/warming catheter. The pigs were then randomized to hypothermia (34°C) or control (37°C). A doppler flow wire was plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Moreover, hypothermia has been shown to improve ion homeostasis, decrease free radical formation, stabilize cellular membranes and prevent intracellular acidosis [21]. It has also been shown to reduce ischemia related coronary t-PA release [28]. In the current experiment hypothermia was found to inhibit a shock-related increase in basal arterial and venous levels of t-PA and also the release of t-PA from the peripheral vascular bed.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Moreover, hypothermia has been shown to improve ion homeostasis, decrease free radical formation, stabilize cellular membranes and prevent intracellular acidosis [21]. It has also been shown to reduce ischemia related coronary t-PA release [28]. In the current experiment hypothermia was found to inhibit a shock-related increase in basal arterial and venous levels of t-PA and also the release of t-PA from the peripheral vascular bed.…”
Section: Discussionmentioning
confidence: 53%
“…The tissue-protective mechanism of action is multi-factorial and partly unknown [20][21][22][23][24][25][26][27]. We recently found that hypothermia reduces ischemia related coronary t-PA release, suggesting a possible role for t-PA as a mechanism for reperfusion injury that may be affected by hypothermia [28].…”
Section: Introductionmentioning
confidence: 99%
“…Like the brain, timing of hypothermia is a major concern in order to rescue the heart from ischemia. Several studies have shown salutary effects of hypothermia in cardioprotection when cooling began prior to the onset of ischemia (Hale and Kloner 1997,van der Pals et al 2009). While consistent and robust effects have been demonstrated, such a paradigm would have limited clinical utility, except in cases of prophylactic cardioprotection in high risk procedures such as aortic aneurysm repair (Coselli and LeMaire 2008) and infants with aortic coarctation and ventricular septal defect (Kanter 2007).…”
Section: Introductionmentioning
confidence: 99%